Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

[tex]\[
\begin{array}{c}
f(x) = \frac{x}{2} + 5 \\
g(x) = 3x + 4
\end{array}
\][/tex]

Calculate the value of [tex]\( g(f(6)) \)[/tex].


Sagot :

To solve the problem, we will follow these steps:

1. Step 1: Calculate [tex]\( f(6) \)[/tex]

The function [tex]\( f(x) \)[/tex] is defined as:
[tex]\[ f(x) = \frac{x}{2} + 5 \][/tex]

Substituting [tex]\( x = 6 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(6) = \frac{6}{2} + 5 \][/tex]
Simplifying the expression:
[tex]\[ f(6) = 3 + 5 = 8.0 \][/tex]

2. Step 2: Calculate [tex]\( g(f(6)) \)[/tex]

First, recall that we have already found [tex]\( f(6) = 8.0 \)[/tex].

Next, the function [tex]\( g(x) \)[/tex] is defined as:
[tex]\[ g(x) = 3x + 4 \][/tex]

So we need to find [tex]\( g(8.0) \)[/tex]:
[tex]\[ g(8.0) = 3(8.0) + 4 \][/tex]
Simplifying the expression:
[tex]\[ g(8.0) = 24.0 + 4 = 28.0 \][/tex]

Therefore, the value of [tex]\( g(f(6)) \)[/tex] is [tex]\( 28.0 \)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.